Wildfire! - Wolff, Ashley (Beach Lane Books, 2021)
Illustrations and easy-to-read text reveal the struggles of forest animals to survive when fire breaks out on Spruce Mountain, and the actions of the firefighters who work through the night to stop the blaze. Contains information about forest fires and fire fighting.